ANALYSIS OF LAPINDO'S MUD INITIATION MOTION AT PORONG RIVER AND ESTUARY - INDRAWAN (NIM 95006015), DERY
One of the scheme for countermeasure Lapindo's mudflow is by flowing the mud to the Porong river. Even though, this scheme could cause negative impact due to river morphology changes. This impact can be seen at the spillway reach nowaday. The aggradation rate in this reach was reported can reach 3 m height. The mud could not be transported to downstream easily. The worst condition is happening in the dry seson where the discharge for transporting the mud has become limited. This research was carried out due to find out the characteristics of sediment initiation motion through the experiment at the flume in the hydraulic laboratory. Analysis was held by comparing the sediment critical shear stress Tcr and riverbed shear stress T0. If T0 > Tcr then the sediment can be transported to downstream, otherwise it will deposit or there will be no sediment motion. Porong riverbed shear stress was find out by using numerical model. Based on this analysis, the minimum requirement of Porong river discharge for transporting sediment can be predicted. Design experiment methodology for sediment initiation motion, mud characteristics and also the capability of Porong river for carrying sediment will be described in this paper.